Role of Different Growth Enhancers as Alternative to In-feed Antibiotics in Poultry Industry - Rafiq, Kazi; Tofazzal Hossain, Muhammad; Ahmed, Rokeya; Hasan, Md. Mehedi; Islam, Rejaul; Hossen, Md. Ismail; Shaha, Sourendra Nath; Islam, Mohammad Rafiqul (Frontiers in Veterinary Science, 2022)
The poultry industry has grown so fast alongside the irrational use of antibiotics to maximize profit and make the production cost-effective during the last few decades. The rising and indiscriminate use of antibiotics might result in the deposition of residues in poultry food products and in the development of resistance to these drugs by microorganisms. Therefore, many diseases are becoming difficult to treat both in humans and animals. In addition, the use of low-dose antibiotics as growth enhancer results in antibiotic residues in food products, which have detrimental effects on human health. On the other hand, many studies have shown that antibiotics administered to poultry and livestock are poorly absorbed through the gut and usually excreted without metabolism. These excreted antibiotics eventually accumulate in the environment and enter the human food chain, resulting in the bioaccumulation of drug residues in the human body. In this regard, to find out alternatives is of paramount importance for the production of safe meat and egg. Therefore, in recent years, much research attention was disarticulated toward the exploration for alternatives to antibiotic as in-feed growth enhancers after its ban by the EU. As a result, probiotics, prebiotics, phytobiotics, spirulina, symbiotic, and their combination are being used more frequently in poultry production. Feed additives therefore gained popularity in poultry production by having many advantages but without any residues in poultry products. In addition, numerous studies demonstrating that such biological supplements compete with antimicrobial resistance have been conducted. Therefore, the purpose of this review article was to highlight the advantages of using biological products instead of antibiotics as poultry in-feed growth enhancers to enhance the production performance, reduce intestinal pathogenic bacteria, and maintain gut health, potentiating the immune response, safety, and wholesomeness of meat and eggs as evidence of consumer protection, as well as to improve the safety of poultry products for human consumption.